Pengaruh Online Customer Review dan Rating Terhadap Keputusan Pembelian yang Dimediasi dengan Kepercayaan - Joy, Stella Kenisya; Tjiptodjojo, Kartika Imasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Easy access to information has provided changes and advances in the marketing world. One of the access to information that helps consumers in their behavior is the reviews and ratings feature, the presence of reviews and ratings features affects various aspects of people's behavior, one of which is trust. The trust formed in consumers will have an impact on purchasing behavior. This research aims to understand the impact of reviews and ratings on people's purchasing behavior through the role of trust. Research was conducted on 105 respondents with the criteria of having visited, read reviews and ratings, and made purchases at Ben and Lou Coffee. The questionnaire was distributed intentionally to respondents who fit the requirements and then tested using the path analysis. Research findings show that online customer reviews and ratings have an influence of 66.9% on purchasing decisions, while there is no influence of online customer reviews and ratings on purchasing decisions mediated by trust.